KESANTUNAN MAHASISWA STKIP HAMZANWADI DALAM MERESPONS PUJIAN - Muhammad Ardian; Herman Wijaya (Universitas Hamzanwadi, 2015)
This research is a qualitative descriptive research that is aimed (a) to describe the students’ strategy of STKIP Hamzanwadi Selong in responding the compliment, and (b) to explain the use of politeness for students of STKIP Hamzanwadi in responding the compliment.The location of this research is conducted at STKIP Hamzanwadi Selong by its research sample are 55 students that is registered actively. Data collection is conducted by using questioner (Discourse Completing Text/ Tes Melengkapi Wacana). The analysis is conducted by using pragmatic match method and extralingual match.The research finding shows that the students use nine strategies to respond compliment. They are (1) token appreciation, (2) comment acceptance, (3) praise upgrade, (4) reassignment, and (5) return, to accept the compliment; and (6) scale down, (7) question, (8) disagreement, and (9) qualification to reject the compliment. In related to the applied of politeness, the students use four maxims Leech, these are tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim.Keywords: politeness, compliment responses, and pragmatic